한국형 성인 ADHD 평가척도 개발 연구 - 강태웅(Taewoong Kang); 김재원(Jae-Won Kim); 반건호(Geon Ho Bahn); 송숙형(Sook Hyung Song); 김준원(Junwon Kim); 김지훈(Ji-Hoon Kim); 김윤정(Yoon-Jung Kim); 김의정(Eui-Jung Kim); 김태호(Tae-Ho Kim); 양수진(Su-Jin Yang); 양재원(Jaewon Yang); 이소영(Soyoung Irene Lee); et al. (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2015)
Objectives : Symptoms of attention-deficit hyperactivity disorder (ADHD) during childhood may persist into adulthood. This study included the development and validation process of the Korean Adult ADHD Rating Scale (K-AARS), which was developed for screening and monitoring treatment of adults with ADHD. Methods : Preliminary questionnaires of the K-AARS were based on the reviews of previous adult ADHD scales and clinical experiences of the board certified child and adolescent psychiatrists in Korea. For this study, 136 adults (18-50 years old) with inattention, hyperactivity and/or impulsivity symptoms were enrolled as ADHD subjects, and compared with 406 control subjects (18-50 years old) without ADHD symptoms. Construct validity was examined using explorative factor analysis and Cronbach's alpha to obtain internal reliability coefficients. Concurrent validity was evaluated by comparison with the Conners' Adult ADHD Rating Scale (CAARS). Results : An explorative factor analysis showed that the K-AARS had 8 factors (inattention, hyperactivity, impulsivity, antisocial personality disorder/conduct disorder/oppositional defiant disorder, impairment, driving, emotional dysregulation, disorganization). K-AARS was highly reliable in terms of internal consistency (Cronbach's alpha 0.77-0.95) and correlation between factors (0.57-0.86). Concurrent validity with the CAARS and discriminant validity were statistically significant. Conclusion : The K-AARS is a valid and reliable measure for assessment of Korean adults with ADHD.